Kualitas Pelayanan dalam Bidang Pemberdayaan Masyarakat di Kecamatan Kedungjajang Lumajang - Rani Nurul Laili Herzegovina; Hayat Hayat (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
Empowerment is an effort to develop the ability and independence of individuals or communities for their needs. In community empowerment, it hope to develop the knowledge, abilities and skills possessed will become asset for individuals, especially people that work in the service sector. The Kedungjajang District Office has an important role to provide some services to the community and help the Government in developing the potential for sovereignty and prosperity for the community. The purpose of this study is to determine how the quality of service in the field of community empowerment in the district of Kedungjajang Lumajang. The research method that used by researchers in this study is a qualitative approach with a descriptive method. The Kedungjajang District Office in the field of community empowerment receive a positive assessment. This is because a qualified management that build the success of village institutions has been fulfilled. The quality of service in the field of community empowerment is carried out in an effort to meet the expectations of the community. Success in the community empowerment is proven by the implementation some programs in several villages, the implementation of the Musrenbang in several villages, the implementation of the BUMDES Guidance and Monitoring Meeting, and the facilitation of the activities like Posyandu, KMPK, and MTQ, KIM, Paskibra, Porkab, Youth, and Scout caravans. . This programs can be reached by dividing the tasks in each Community Empowerment District staff and assisted by the sub-district head.